Exploring the role of servant leadership in developing accountability and trust in a college in Lagos State, Nigeria - Idowu, Adebimpe Olusola (My University, 2021)
Servant leaders are ethical leaders who lead with high moral standards to meet the vision and mission of the organisation. This single-case, qualitative study sought to explore the role of servant leadership in developing accountability and trust in a college located in Lagos State, Nigeria. Five participants were consulted for semi-structured interviews to generate data. The study was informed by Sipe and Frick‘s (2015) Model of Servant leadership. The model posits seven principles which they refer to as pillars to uphold an organisation and these are: being a person of character, putting people first, communicate skillfully, be a compassionate collaborator, having foresight, be a system thinker, lead with moral authority. Hence, collegeleaders are expected to possess these behaviours in order to be accountable and to gain the trust of education stakeholders. It was found out that some lecturers, because they were not occupying executive positions in the college, felt that they were not leadersand this indicated knowledge gaps among them All the participants agreed with the notion of servant leadership and concurred that if these behaviours were in practice in the college, it could be possible to achieve the college goals. Another finding showed that although the college frowns at lack of accountability and distrust, yet the system was not entirely free from it. Lack of accountability was attributed to factors like upbringing, peer group pressure and greed. There were some shortfalls from the researched college which made it possible for college leaders and lecturers not to be accountable. This study recommends remedial actions such as training of college leaders on servant leadership to all college personnel to eliminate knowledge gaps in their roles at the college. This could also constitute issues of accountability and trust and the role of college leadership in this. This study contends that it is the responsibility of those in leadership and management to ensure servanthood, accountability and trust in the researched college
A research report submitted in the partial fulfillment of the requirements for the degree of Master of Education (MED) by course work and research report to the Faculty of Humanities, Wits School of Education, University of Witwatersrand, 2021